Evaluasi Desain User Interface Berdasarkan User Experience Pada Aplikasi Perpustakaan Digital Isleman - Sari, Kartika Puspita; Zulaikha, Sri Rohyanti; Mubarokah, Adzkiyah (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Research related to evaluation of user interface design based on user experience in Isleman Digital Library Application aims to evaluate the user interface design of Isleman digital library application based on user experience. A qualitative approach is used as a research method, the collection of material through interviews, observation and analysis of related documentation. The results showed that the user interface design of the Isleman digital library application received positive responses from users. They find the design intuitive, easy to use, and present information clearly. Users also appreciate the program's clean layout and easy navigation, which allows them to easily find and access the library resources they need. Features such as efficient search, responsive display, and integration with other library management systems have also received positive reviews from users. These features are designed to improve usability and help users find and manage library materials more efficiently. However, some users provided feedback on minor improvements to the UI design, such as improved icon appearance and text clarity in some parts of the app. Based on the results of this study, several corrective steps are suggested to improve the user experience of the Isleman digital library application. These steps include visual enhancements, clarifying text and instructions, and changing the layout to make it more responsive and user-friendly. This research makes a major contribution to understanding the user's perspective on the user interface design of Isleman's digital library and provides recommendations for improvements that can be applied to improve the overall user experience.